Research of Optimization of Gear Rattle of Manual Transmission in Passenger Car - Wang Lei; Wu Xuncheng; Ge Bing (Jixie chuandong)
The vibration and noise generation mechanism of the gear rattle in manual transmission is analyzed.According to the measurement of the size and the test of the NVH,the gear rattle in manual transmission is caused by the severe torque fluctuation of input shaft.The working principle of the dual mass flywheel（DMF） damping the gear rattle noise in manual transmission is analyzed.Through the experiment,the DMF can effectively damp the torque fluctuation of input shaft is verified,the gear rattle of the passenger car manual transmission can be controlled in a reasonable range as well.